Analisis Usability Terhadap Kepuasan dan Loyalitas Website - Evi Susanti; Anuar Rasyid; Nurjanah (Jurnal Gema Pustakawan, 2021)
This study aims to analyze the effect of usability on the satisfaction and loyalty of visitors to the Riau University Library website. Usability is one of the factors used to measure the success of a website. The higher the level of usability, the level of user satisfaction will be higher as well as loyalty. This study uses a quantitative approach. The analytical method used is Structural Equation Modeling (SEM). The research was conducted on the Riau University Library website with a population of 911,156 website visitors, while the sample used was 200 people. The results showed that usability had a significant effect on satisfaction directly but not significantly on loyalty. While satisfaction has a significant effect on loyalty.